Autologous serum therapy in chronic spontaneous urticaria: useful in both ASST positive and negative patients - Talwar, Vijayalakshmi; Bhaskar, Puspha (International Journal of Research in Dermatology, 2022)
Background: Chronic urticaria is a common disorder that affects 0.1% of the population. Point prevalence is between 0.5 and 1.0% for chronic spontaneous urticaria. Functional IgG antibodies against IgE or high-affinity IgE receptors can be detected in 25-30% of patients with chronic spontaneous urticaria. Autologous serum therapy is a novel and cost-effective therapy. The aim of the study was to evaluate Autologous serum therapy’s (AST) efficacy in chronic urticaria patients. Methods: 106 patients with chronic urticaria were enrolled. Patients were categorized into two groups based on autologous serum skin therapy- ASST positive and ASST negative. Intramuscular injection of 0.05 ml/kg of autologous serum was injected every week for up to 9 weeks. Urticaria activity scoring (UAS) questionnaire was used to quantify the symptoms before the therapy and at nine weeks. Results: Significant improvement in urticaria activity score was noted in both groups of the patients from the baseline and at nine weeks. (UAS reduced from 15.3 to 10.8 in ASST positive patients, and in ASST negative patients, UAS decreased from 16.2 to 10.1). Conclusions: Both ASST positive and ASST negative patients showed significant improvement at nine weeks after starting autologous serum therapy. AST can be an effective modality for both patients.